Head size and growth in the very preterm infant: a literature review - Lee KA; Hayes BC (Dove Medical Press, 2015)
Karla A Lee, Breda C Hayes Rotunda Hospital, Dublin 1, Leinster, Ireland Objective: To review the literature investigating head size and examine head growth in relation to neurodevelopmental outcomes and neuroimaging data in the very preterm infant.Methods: Systematic literature review of studies published in the following databases: PubMed/Medline, Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index to Nursing and Allied Health (CINAHL), and Excerpta Medica dataBASE (EMBASE). Studies in the English language published between January 2005 and August 2013 were examined. Subjects were infants born at ≤32 weeks of gestation. Main outcome measures included head growth, neurodevelopmental outcomes, and correlation between head size and neuroimaging.Results: Thirty-four articles comprising 9,394 infants met inclusion/exclusion criteria. Of these, 31 studies (6,592 subjects) report head growth data measured at two or more time points. Neurodevelopmental outcome at ≥2 years was reported by eleven studies (3,817 subjects). Nine studies (2,363 subjects) included neuroimaging data. Catch-up head growth was found to occur in the first year after birth. Poor nutrition was linked with poorer head growth. Small head size was associated with poor psychomotor and mental skills, higher rates of cerebral palsy, and autism. However, suboptimal head size at birth was not predictive of poor outcome, unless it persisted. Head size appears to correlate with brain volume at term. Associations between white matter abnormalities have been found by ultrasonography. In contrast, in magnetic resonance imaging (MRI) studies, gray matter seems to be the most susceptible to impairments during postnatal growth.Conclusion: Head growth in early neonatal life is of importance. Avoiding growth impairment during neonatal care may allow for optimal cortical development. Many factors impact upon early head growth, particularly appropriate nutrition. There is no clear correlation between neuroimaging and head growth and this is an area deserving future research. Keywords: head growth, head size, outcome, premature